Effects of low temperature on flowering and the expression of related genes in Loropetalum chinense var. rubrum - Zhang, Damao; Chen, Qianru; Zhang, Xia; Lin, Ling; Cai, Ming; Cai, Wenqi; Liu, Yang; Xiang, Lili; Sun, Ming; Yu, Xiaoying; Li, Yanlin (Frontiers in Plant Science, 2022)
Loropetalum chinense var. rubrum blooms 2-3 times a year, and the autumn flowering period has great potential for development and utilization, but the number of flowers in the autumn is much less than that in the spring. Taking ‘Hei Zhenzhu’ and ‘Xiangnong Xiangyun’ as materials, the temperature of 6-10 ℃ was used to arranging experiments, to explore the effect of low temperature on the flowering of L. chinense var. rubrum and the expression of related genes.Found that after 45 days of low-temperature culture, ‘Hei Zhenzhu’ and ‘Xiangnong Xiangyun’ began to bud after 24 and 21 days of continuous culture in 25 ℃, and then bloom on the 33rd and 30th days. The group(CK) that cultivated at 25°C didn't flowering. In 7-28 days, the growth rate of buds showed the law of ‘up-down’. Meanwhile, the chlorophyll fluorescence decay rate (Rfd) of all materials showed a 'down-up-down' law and reached a higher level on the 21st day, the changing trend of the non-photochemical quenching coefficient (NPQ) is consistent with Rfd, the photochemical quenching coefficient (QP) fluctuates regularly around 0.05. The expression of AP1 and FT similar genes increased gradually after T0 and reached the highest expression on the 14th and 28th days, the expression of both genes in low-temperature group was higher than that in CK. The expression of FLC, SVP, and TFL1 similar genes augustus27517, augustus15211, and augustus62587 were decreased with low-temperature culture. The expression of augustus27517 and augustus62587 in low-temperature were significantly lower than those in CK. The expression of GA3 similar genes were significantly higher than those in the CK, and their expression increased with the increase of low-temperature culture time. Studies have shown that low-temperatures can promote the flowering of L. chinense var. rubrum, and it may be the main reason why the number of flowers of L. chinense var. rubrum in spring is greater than that in autumn. We also found that gibberellin plays an important role in this process. It may be possible to regulate the flowering of L. chinense var. rubrum by simply spraying exogenous gibberellin instead of the promoting effect of low temperature.